EXPLORING THE ROLE OF LEXICOGRAPHY IN LINGUISTICS (Konferensiyalar | Conferences, 2024)
This article gives information about the role of lexicography in linguistics , exploring its types, history, academic disciplines , problems, and importa nce in learning languages. Lexicography plays a crucial role in linguistics as it focuses on the study of dictionaries and the principles involved in compiling, organizing, and presenting lexical information. The main goals of lexicography are to provide a reliable, comprehensive account of a spoken language. The lexicographer must research, organize, define, and compile the words in a dictionary. For each dictionary entry, the lexicographer provides a definition, a pronunciation, a list of synonyms, an exa mple of the word being used, and sometimes its etymology.